1260 High Tidal Volume Non-invasive Ventilation Required to Treat Obesity Hypoventilation. (27th May 2020) - Rezayat, Talayeh; Beggs, Abigail; Avidan, Alon Y; Javaheri, Shahrokh
Abstract: Introduction: Current guidelines recommend CPAP or non-invasive ventilation with tidal volume (VT) <10ml/kg of ideal body weight (IBW) for the treatment of obesity hypoventilation. However, in select patients with significant obesity hypoventilation, this recommendation may not be sufficient to resolve nocturnal hypoventilation. Report of Case: A 35 y/o male with hypertension and class III obesity (BMI 58 kg/m2) was referred for evaluation of acute respiratory failure with hypoxia and hypercapnia. ABG demonstrated daytime PCO2 of 71 mmHg. Patient reported sleep fragmentation, snoring, choke awakenings, poor concentration, depression and sleep attacks. PSG demonstrated severe OSA, with an AHI of 154 events/hour, persistent hypoxia and hypercapnia with a SpO2 nadir of 50% and ET-CO2 of 83 mmHg during REM sleep. Respiratory events persisted with CPAP and bilevel, up to a setting of 25/16. Average volume assured pressure support (AVAPS) S/T titration study was performed and resolved sleep apnea at settings of IPAP 24-30, EPAP 4-15, VT 790 (10 mL/kg IBW), 0.5 LPM O2, rate 16. The patient reported having had the best sleep of his life at the end of this study and has since been started on treatment. Conclusion: Treatment of OHS should be individualized and may require use of tidal volumes above 10ml/kg for effective treatment. We suggest that in super morbidly obese patients, with extremely noncompliant respiratory system, larger than recommended tidal volume is necessary to ventilate the patient and improve gas exchange. The sustained higher pressures achieved by AVAPS to impose the augmented tidal volume more effectively ameliorate OSA, by keeping the upper airway open. Higher pressures achieved also could elevate FRC, not only increasing oxygen stores, but also contributing to maintenance of open upper airway through its tethering effect. Further physiological studies are needed in super morbidly obese patients comparing low and high tidal volumes.